Evaluation of Red Cell Distribution Width and Platelet Distribution Width as a Predictor of Iron Stores; A Comparative Cross-Sectional Study - Salman, Alea Farhan; Nori, Wassan; Hussein, Zina Abdullah; Kassim, Mustafa Ali Kassim; Pantazi, Alexandru Cosmin (AL-Kindy College Medical Journal, 2024)
Background: Iron deficiency (ID) is a global problem that affects women more prevalently, causing vast health consequences. Screening by hemoglobin and serum ferritin is currently applied for ID. Recently, interest in complete blood count parameters (CBC) has emerged for its close relationship with body iron stores. Objectives: to examine whether hematological indices of CBC [namely red cell distribution width-coefficient of variation (RDW-CV) and platelets distribution width-coefficient of variation (PDW-CV)] can serve as a predictor for ID in Iraqi women. Subjects and Methods: A cross-sectional study at the National Center of Hematology recruited 200 women into a study group: 100 anemic women and 100 healthy controls. Their demographics, hematological indices, and iron indicators (serum ferritin, iron, total iron binding capacity (TIBC), and transferrin saturation) were collected. Results: The RDW-CV and platelet counts were statistically higher in the IDA cases, while PDW was lower. RDW had significant correlation to serum ferritin (r=-0.2, P=0.04), while PDW was significantly linked to serum ferritin (0.22, P=0.03) TIBC (r=-0.24, P=0.02) and TSP (r-0.23, P=0.02). RDW had the highest positive and negative predictive values, with 84 and 97 %, respectively, followed by platelet counts, which scored 72 and 78 %, respectively. RDW-CV cutoff value scored the highest sensitivity, 97%, and specificity, 82%, in discriminating ID cases from healthy controls with an area under the curve of 0.98 and P<0.001. Conclusions: RDW showed significant correlations to iron indicators with strong discriminating power and high positive predictive value. RDW accessibility and affordability make them recommendable markers in earlier screening for ID.